Syngas from palm oil mill effluent (POME) steam reforming over lanthanum cobaltite : effects of net-basicity - Cheng, Yoke Wang; Chong, Chi Cheng; Lee, Soon Poh; Lim, Jun Wei; Wu, Ta Yeong; Cheng, C. K. (Elsevier, 2020)
Steam reforming (SR) of palm oil mill effluent (POME) over net-basic LaCoO3 was optimised for syngas production (FSyngas) and degradation efficacies (XP) by tuning temperature (T), POME flow rate (V˙POME), catalyst weight (Wcat), and particle size (dcat). Net-basicity of LaCoO3 facilitated the adsorption of Lewis acid CO2, thereby assisted carbon removal via reverse Boudouard reaction. POME SR over LaCoO3 was promoted by using (i) higher T (endothermicity), (ii) greater V˙POME (larger partial pressure at constant weight-hourly-space-velocity and total feed rate), (iii) larger Wcat (longer residence time for POME vapour), and (iv) smaller dcat (higher surface area to volume ratio). Nevertheless, the catalytic activity of LaCoO3 declined with (i) severe coking and sintering deactivation (T≥973 K), (ii) carbon-encapsulation (V˙POME  = 0.10 mL/min), (iii) agglomeration (Wcat>0.3 g), and (iv) pore occlusion (dcat<74 μm). Hence, the optimum conditions of POME SR over LaCoO3 were T  = 873 K, V˙POME  = 0.09 mL/min, Wcat  = 0.3 g, and dcat  = 74–105 μm. The optimised process able to produce syngas at a rate of 86.60 μmol/min whilst degrading POME to a less polluted liquid condensate (COD = 435 mg/L and BOD5 = 62 mg/L).